So not mothers: responsibility for surrogate orphans. Issue 8 (12th April 2018) - Parks, Jennifer A; Murphy, Timothy F
Abstract : The law ordinarily recognises the woman who gives birth as the mother of a child, but in certain jurisdictions, it will recognise the commissioning couple as the legal parents of a child born to a commercial surrogate. Some commissioning parents have, however, effectively abandoned the children they commission, and in such cases, commercial surrogates may find themselves facing unexpected maternal responsibility for children they had fully intended to give up. Any assumption that commercial surrogates ought to assume maternal responsibility for abandoned children runs contrary to the moral suppositions that typically govern contract surrogacy, in particular, assumptions that gestational carriers are not 'mothers' in any morally significant sense. In general, commercial gestational surrogates are almost entirely conceptualised as 'vessels'. In a moral sense, it is deeply inconsistent to expect commercial surrogates to assume maternal responsibility simply because commissioning parents abandon children for one reason or another. We identify several instances of child abandonment and discuss their implications with regard to the moral conceptualisation of commercial gestational surrogates. We conclude that if gestational surrogates are to remain conceptualised as mere vessels, they should not be expected to assume responsibility for children abandoned by commissioning parents, not even the limited responsibility of giving them up for adoption or surrendering them to the state.